PENGARUH POLA ASUH ORANG TUA DAN PEMBELAJARAN GURU KEWIRAUSAHAAN TERHADAP PERCAYA DIRI SISWA SMK NEGERI 5 SURABAYA - Sriwulandhari, Elfiana; Suratman, Bambang (UNIVERSITAS NEGERI SURABAYA, 2013)
This study aims to determine 1) the influence of the parenting patterns on students self confidence 2) the influence of Entrepreneurship teacherss instruction on students self confidence and 3) the influence of parenting patterns and Entrepreneurship teachers instruction on students self confidence at SMK Negeri 5 Surabaya. The population covers 650 students of SMK Negeri 5 Surabaya grade X. Random sampling technique was employed to select 227 students among them. Data were collected by using questionnaires and analyzed by using multiple linear regression analysis. The finding indicates that the partial test (t test) positively confirms the influence of the parents parenting on students self confidence (3.139; d.f.: 0.002) and that Entrepreneurship teachers instruction also significantly affects students self confidence (5.227; d.f.: 0.000). Again, on the basis of the F test, the study concludes that parenting patterns and teachers instruction simultaneously affect the students self confidence (23.910 d.f.: 0.000). Parents are, therefore, advised to apply the appropriate parenting to their children. Also, teachers of SMK Negeri 5 Surabaya are suggested to improve their professionalism in nurturing students character so that students will have better self confidence.